Impact of Attached File Formats on the Performance of ChatGPT-4 on the Japanese National Nursing Examination: Evaluation Study - Kazuya Taira; Takahiro Itaya; Shuntaro Yada; Kirara Hiyama; Ayame Hanada (JMIR Nursing)
AbstractThis research letter discusses the impact of different file formats on ChatGPT-4’s performance on the Japanese National Nursing Examination, highlighting the need for standardized reporting protocols to enhance the integration of artificial intelligence in nursing education and practice.